Effect Of Product Quality And Service On Customer Loyalty With Customer Satisfaction As An Intervening Variable (Study On Coffee Shop In Medan) - Tirtayasa, Satria (International Journal of Science, Technology & Management, 2022)
This study is to determine the effect of product quality on consumer loyalty, to determine the quality of service to consumer loyalty. To know the effect of product quality and service quality on customer satisfaction. The type of research used is a type of quantitative research. In this study used 105 sample. Data collection techniques used by researchers in conducting this study is to use an online questionnaire. Data analysis technique of this study is SEM-PLS. From this study it was found that the influence of product quality on customer loyalty is a positive effect and not significant. With a value of 0.163 and P – Values 0.000 < 0.05. From this study it was found that the influence of product quality on customer satisfaction is a positive effect and not significant. With a value of 0.000 < 0.05. From this research found that the influence of customer satisfaction on customer loyalty is a positive and significant effect. From this research found that the influence of customer satisfaction on customer loyalty is a positive and significant effect. From this study it was found that the real effect is direct it is shown by the value of the original sample on the indirect effect of 0.000 < 0.05, meaning that customer satisfaction plays a role in mediating product quality to customer loyalty. From this study it was found that the real effect is direct it is shown by the value of the original sample on the indirect effect of 0.000 < 0.05, meaning that customer satisfaction plays a role in mediating service to customer loyalty.